Subsídios à implantação de aterro sanitário:um estudo de caso em Baturité-CE - Paula, Francinize de Sousa (2009)
The present research it approached as to generate subsidies for implantation of landfills in the Baturité city. For this, the methodology of Ranieri (2000) was used to make thematic maps through of software Idrisi, regarding environmentals factors (use of the natural resources, pedology, hydric resources, geomorphology, vegetation, geology). Later, was made a new classification of characteristics of the maps for identify areas more adjusted for implantation of landfills generating the final map of aptitude. In this manner, the results showed in the research presented a total area of 1.475km2 , regarding the selected area respecting the minimum limits of 2,0 km from the center of the city and maximum limits of 15km, being however only 5,9km2 of it, that is considered adjusted for implantation of landfills through the overlapping of the specified maps. Concluded, therefore, that the study area is not prepared enough for receive the activity of landfills because the its size is minimum still that presenting favorable geoenvironmentals characteristics. In addiction, the results of gravimetrical composition it got high contents of organic substance justifying the necessity of landfills. However, on the basis of the simulation of the final map of aptitude has little area. Concluded, also, that there is the necessity of 1,5 ha of the area for to implant the landfills but the simulation did not point this area all.